Determination of reference range for high sensitive troponin T among end stage renal disease patients in Hospital Raja Perempuan Zainab II, Kelantan - Zamri, Wan Nur Aimi Wan Mohd (2020)
In End-Stage Renal Disease (ESRD), troponin T can be elevated even without cardiac ischemia thus diagnosing an Acute Coronary Syndrome (ACS) in these patients is often difficult. The objectives of our study were to evaluate the high-sensitive troponin T (hs-TnT) level and to determine its reference range in dialysis-dependent ESRD patients without ACS. This crosssectional study was conducted at Hemodialysis Unit of the Hospital Raja Perempuan Zainab II, Kelantan from January 2018 and February 2019. Medical records of ESRD patients on dialysis were reviewed. Demographic data, etiology of ESRD, type, and duration of dialysis were recorded. Subjects with no recent (<30 days) ACS were included in this study. Predialysed hs-TnT was measured using Cobas e411. A total of 150 ESRD patients were recruited with 62% were females and majority (94%) were Malays. The mean (SD) age was 45.19 (16.36) years. The hs-TnT median (IQR) was 59.20 ng/L (83.41 ng/L). 149 (99%) of our subjects had hs-TnT level above cut-off in which 98.2% and 100% were among hemodialysis (HD) and continuous ambulatory peritoneal dialysis (CAPD) patients respectively. The 95% reference ranges for hs-TnT level in ESRD patients were 11.86– 379.52 ng/L (2.5th percentile 90% CI=9.67-14.51 ng/L and 97.5th percentile 90% CI=310.06- 465.31 ng/L) with the 99th percentile upper reference limit (URL) value of 526.40 ng/L (90% CI=430.13-645.48 ng/L). This study demonstrated that almost all of our subjects had elevated troponin T above the cut-off value. Knowledge of the reference range and URL may serve as guidance to the clinicians when managing ESRD patients presented with possible ACS and considered as a cut-off value for the diagnosis of ACS in ESRD patients.